EdGEO:: Helping Teachers Teach Earth Science - Van der Flier-Keller, Eileen; Clinton, Laura; Haidl, Fran (Geoscience Canada, 2009)
SUMMARY EdGEO is a national program that supports Earth science workshops for Canadian teachers. Geoscientists and teachers work collaboratively to develop and deliver these curriculum-linked workshops, which provide teachers with the classroom resources, enhanced knowledge, and increased confidence to teach Earth science more effectively. Grants of up to $3000 per workshop are available from EdGEO for this purpose. The ability of EdGEO to advance its vital mission relies on the generous support of scientific associations, corporations, foundations and individuals. With increased funding, EdGEO’s future will see the compilation of EdGEO lesson plans from workshops across Canada, and the development of learning activities to integrate Earth science into physics, chemistry, biology and mathematics; all these resources will be available for download from the EdGEO web site.